Validation of Hindi version of the obstetric quality of recovery score-11 (ObsQoR-11 H) following elective caesarean section - Sunanda Gupta; Savita Choudhary; Vidhu Choudhary; Kajal Jain; Nidhi Bhatia; Apoorva Gupta (Indian Journal of Anaesthesia, 2023)
Background and Aims: Obstetric quality of recovery score-11 (ObsQoR-11) was developed in English to evaluate the quality of recovery in the caesarean section. We aimed to validate the Hindi version of ObsQoR-11 (ObsQoR-11H) for Hindi-speaking patients to evaluate the quality of recovery following the elective caesarean section. Methods: The ObsQoR-11 was translated into Hindi and assessed for validity, acceptability and feasibility. The questionnaire was administered postoperatively at 24 and 48 hours, and the Global Health Numeric Rating Scale (NRS) was used to evaluate recovery. Results: The mean (standard deviation [SD]) (95% confidence interval [CI]) ObsQoR-11 H was 75.94 (4.09)(95% CI 75.1, 76.7) and 80.25 (4.08)(95% CI 79.5, 81) at 24 and 48 hours, respectively. The mean (SD) (95%CI) Global Health NRS scores were 71.22 (5.97)(95% CI 70, 72.4) and 77.37 (5.79)(95% CI 76.2, 78.5) at 24 and 48 hours, respectively. Convergent validity showed a strong correlation between ObsQoR-11H and Global Health NRS (Spearman's correlation coefficient [rs] >0.8 and 0.78) scores at 24 and 48 hours, respectively. Discriminant validity was significant in appreciating the difference between good and poor recovery (P < 0.001). Split-half coefficient of 0.69 and 0.65 and Cronbach's alpha (α) of 0.91 and 0.82 at 24 and 48 hours suggested good score reliability. The acceptability and feasibility of the score were also good. Conclusion: The ObsQoR-11H discriminated well between 'good' and 'poor' recovery and correlated strongly with Global Health NRS scores. It was found to be a valid, reliable, acceptable and feasible tool for psychometric recovery evaluation after elective caesarean section in Hindi-speaking women.